Sexual selection in complex communities: Integrating interspecific reproductive interference in structured populations. (16th April 2019) - McDonald, Grant C.; Gardner, Andy; Pizzari, Tommaso
Abstract: The social structure of populations plays a key role in shaping variation in sexual selection. In nature, sexual selection occurs in communities of interacting species; however, heterospecifics are rarely included in characterizations of social structure. Heterospecifics can influence the reproductive outcomes of intrasexual competition by interfering with intraspecific sexual interactions (interspecific reproductive interference [IRI]). We outline the need for studies of sexual selection to incorporate heterospecifics as part of the social environment. We use simulations to show that classic predictions for the effect of social structure on sexual selection are altered by an interaction between social structure and IRI. This interaction has wide‐ranging implications for patterns of sexual conflict and kin‐selected reproductive strategies in socially structured populations. Our work bridges the gap between sexual selection research on social structure and IRI, and highlights future directions to study sexual selection in interacting communities.